(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
Entrepreneurship is the process of creating something new by using time and activities accompanied by capital and risk and receiving rewards and satisfaction as well as personal freedom (Mintardjo et al., 2020). In Indonesia, interest in entrepreneurship is still relatively low. This is evidenced by the still large number of unemployed, which is caused by a lack of public awareness of the availability of jobs that can absorb all graduates or job applicants. Based on the situation analysis that has been carried out through initial observation activities and interviews with the two partners, it was found that entrepreneurship learning or training in schools is not optimal, so it still needs to be taught to students. Based on these problems, the purpose of this community service activity is for students to understand the concept of entrepreneurship, and students get ideas to start running business activities, as well as apply the knowledge gained in the business they run. The method used in this activity is training (lectures and practices) that involve students directly. This activity was carried out in two meetings at each partner school. Based on the results of the response questionnaire filled out by the training participants, it was found that the students felt happy and became motivated to entrepreneurship by participating in the training activities, so it can be concluded that the activities were carried out well.